2017
DOI: 10.1055/s-0043-109560
|View full text |Cite
|
Sign up to set email alerts
|

Driving Problems in the Elderly and Cognitively Impaired

Abstract: Driving ability in the elderly and cognitively impaired is of growing demographic relevance. Driving represents a complex task for which multiple central resources are needed. In mild cognitive impairment and dementia, we need to closely monitor driving ability, as it gets irrecoverably lost in the course of the disease. In normal aging, people are often able to self-regulate driving behavior with respect to their medical conditions. Some studies demonstrated that older drivers perform well compared with young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…In this research, further examination of the cognitive tests revealed that memory, reaction and judgment ability were all associated with the age of the drivers because all the test scores had a significant influence between the two groups. This was also consistent with Robert's conclusion that differences in cognitive function increase with age [15].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this research, further examination of the cognitive tests revealed that memory, reaction and judgment ability were all associated with the age of the drivers because all the test scores had a significant influence between the two groups. This was also consistent with Robert's conclusion that differences in cognitive function increase with age [15].…”
Section: Discussionsupporting
confidence: 90%
“…The brief mental status examinations mainly consist of the Montreal Cognitive Assessment (MoCA) and the Mini Mental State Examination (MMSE) [10,11]. Awareness allows an individual to engage in appropriate self-monitoring while driving, and subsequently make important decisions regarding compensatory strategies [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Although only one of the skills may be impaired, management of elderly patients with major neurocognitive disorder becomes both a problem for the family and a public health problem, in that elderly drivers should be evaluated. 29 There is a need to review the praxis items within CAMCOG, so as to be able to assess the skills of elderly drivers. Impaired driving skills are only one example of the negative debilitating effects of apraxia, but it is important to emphasize the general importance of evaluation of praxis, as one of the indicators of cognitive fragility among elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, neither Alzheimer's nor Parkinson's disease has specific time frames or markers that clearly indicate when an individual is no longer safe to drive (Hebert, Martin-Cook, Svetlik, & Weiner, 2003;Turner, Liddle, & Pachana, 2017). Accordingly, the literature on driving cessation is dominated by efforts to develop and evaluate measures of driving ability (Bennett, Chekaluk, & Batchelor, 2016;Brown & Ott, 2004;Cameron et al, 2017;Haussmann, Buthut, & Donix, 2017;Piersma et al, 2018). Off-road tests, such as the Clinical Dementia Rating Scale or the Mini-Mental State Examination, have not been found to be sufficient measures of driving performance or risk level to determine when an individual is unsafe to drive (Bennett et al, 2016;Davis & Ohman, 2017).…”
Section: Introductionmentioning
confidence: 99%